1999
DOI: 10.1002/(sici)1099-1085(199907)13:10<1423::aid-hyp819>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of throughfall and stemflow in multi-strata agroforestry, perennial monoculture, fallow and primary forest in central Amazonia, Brazil

Abstract: The partitioning of rain water into throughfall, stem¯ow and interception loss when passing through plant canopies depends on properties of the respective plant species, such as leaf area and branch angles. In heterogeneous vegetation, such as tropical forest or polycultural systems, the presence of dierent plant species may consequently result in a mosaic of situations with respect to quantity and quality of water inputs into the soil. As these processes in¯uence not only the water availability for the plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 14 publications
0
41
0
6
Order By: Relevance
“…The stemflow component of interception was ignored because it was assumed to be a small volumetric flux, i.e. !2% of rain (Schroth et al, 1999;Neal et al, 1993). The canopy conditions were modeled as either completely wet or completely dry for any 30 min period .…”
Section: Modeled Conductance and Evapotranspirationmentioning
confidence: 99%
“…The stemflow component of interception was ignored because it was assumed to be a small volumetric flux, i.e. !2% of rain (Schroth et al, 1999;Neal et al, 1993). The canopy conditions were modeled as either completely wet or completely dry for any 30 min period .…”
Section: Modeled Conductance and Evapotranspirationmentioning
confidence: 99%
“…Hydrologists have demonstrated that species composition does have a detectable and substantial impact on throughfall amounts (Mahendrappa, 1989;Brown and Iles, 1991;Cape et al, 1991;Thimonier, 1998;Schroth et al, 1999;Lilienfein and Wilcke, 2004). At Devilla Forest, in northern Britain, Cape et al (1991) found that throughfall varied substantially between Pinus sylvestris L. (Scots pine) and Larix decidua L. (larch) over two successive years of measurement using a series of fixed gauges.…”
Section: Interspecific Variation: Volumementioning
confidence: 99%
“…stem diameter, crown geometry). We are therefore forced to ascribe, as were Schroth et al, 1999Schroth et al, ,2001 the difference in stemflow yields among trees to undefined structural variables in the canopy.…”
Section: Stemflowmentioning
confidence: 99%